Load-bearing mechanism and engineering application of a heavy-duty transfer steel platform supported by basement columns - Meijun Shang; Xuemei Li (PLoS ONE, 2025)
Heavy lifting operations performed on basement roof slabs often impose concentrated loads that may cause local stress concentrations, cracking, or even structural failure. To address this issue, this study proposes a heavy-load transfer steel platform supported by basement columns, which effectively isolates the lifting load from the roof slab to ensure structural safety. The load-bearing mechanism of the proposed steel platform was analyzed theoretically, and finite element analysis (FEA) was employed to evaluate the stresses and deflections of key members. A particle swarm optimization (PSO) algorithm was integrated with the FEA model to optimize the cross-sectional dimensions of the primary beams, secondary beams, and foundation boxes, achieving a balance between load-bearing capacity and cost efficiency. The method was validated through field measurements from the Phase I project of the Hangzhou Convention and Exhibition Center, where strain gauges and displacement sensors were installed at critical positions for real-time monitoring. The measured data showed good agreement with the FEA predictions, with deviations of 5.2% for steel beam stress and 3.7% for foundation box deflection. After optimization, the material usage of the foundation boxes, secondary beams, and primary beams was reduced by 44.68%, 58.33%, and 55.00%, respectively, resulting in an overall material cost reduction of 52.67%. The results demonstrate that the proposed platform effectively mitigates stress concentration and prevents cracking of basement roof slabs under large-tonnage hoisting conditions. The structure exhibits high safety, efficiency, and reusability. Furthermore, the use of recyclable steel materials aligns with green construction and sustainability principles. Future research should explore the platform’s applicability under irregular column layouts and dynamic loading conditions.